Differential changes in steroid hormones before competition in bonobos and chimpanzees - Wobber, Victoria (National Academy of Sciences, 2010)
A large body of research has demonstrated that variation in competitive behavior across species and individuals is linked to variation in physiology. In particular, rapid changes in testosterone and cortisol during competition differ according to an individual's or species’ psychological and behavioral responses to competition. This suggests that among pairs of species in which there are behavioral differences in competition, there should also be differences in the endocrine shifts surrounding competition. We tested this hypothesis by presenting humans’ closest living relatives, chimpanzees (Pan troglodytes) and bonobos (Pan paniscus), with a dyadic food competition and measuring their salivary testosterone and cortisol levels. Given that chimpanzees and bonobos differ markedly in their food-sharing behavior, we predicted that they would differ in their rapid endocrine shifts. We found that in both species, males showed an anticipatory decrease (relative to baseline) in steroids when placed with a partner in a situation in which the two individuals shared food, and an anticipatory increase when placed with a partner in a situation in which the dominant individual obtained more food. The species differed, however, in terms of which hormone was affected; in bonobo males the shifts occurred in cortisol, whereas in chimpanzee males the shifts occurred in testosterone. Thus, in anticipation of an identical competition, bonobo and chimpanzee males showed differential endocrine shifts, perhaps due to differences in perception of the situation, that is, viewing the event either as a stressor or a dominance contest. In turn, common selection pressures in human evolution may have acted on the psychology and the endocrinology of our competitive behavior.